Efficiency and equity Effects of Taxing the Financial Sector: Lessons from a CGE Model for Belgium - Chisari, Omar Osvaldo (2016)
This paper assesses the effects of applying VAT or a sales tax on (intermediate or final) sales of the financial sector. It uses a CGE Model calibrated for a small open economy. It highlights the differentiated sectoral and redistributional effects of these taxes and shows the importance of the financial openness of the economy on these results.